Analysis of the system efficiency of an intermediate temperature proton exchange membrane fuel cell at elevated temperature and relative humidity conditions. (15th March 2016) - Jeon, Seung Won; Cha, Dowon; Kim, Hyung Soon; Kim, Yongchan
Highlights: System efficiency of PEMFC is evaluated at elevated temperature and humidity. Operating parameters are optimized using response surface methodology. The optimal operating parameters are T = 90.6 °C, RH = 100.0%, and ζ = 2.07. The power output and system efficiency are 1.28 W and 15.8% at the optimum. The system efficiency can be effectively improved by increasing relative humidity. Abstract: Humidification of the membrane is very important in a proton exchange membrane fuel cell (PEMFC), to maintain high ionic conductivity. At an elevated temperature, a large amount of thermal energy is required for humidification because of the exponentially increased saturation vapor pressure. In this study, the system efficiency of a PEMFC was evaluated by considering the heat required for preheating/humidification and compression work. Three-dimensional steady-state simulations were conducted using Fluent 14 to simulate the electrochemical reactions. The operating conditions were optimized using response surface methodology by considering both the fuel cell output and system efficiency. In addition, the effects of operating parameters such as the temperature, relative humidity, and stoichiometric ratio were investigated. The system efficiency can be improved more effectively by increasing relative humidity rather than increasing operating temperature because the ionic conductivity of the membrane was strongly influenced by the relative humidity.